2015
DOI: 10.1016/j.apgeochem.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and antimony geochemistry of mine wastes, associated waters and sediments at the Giant Mine, Yellowknife, Northwest Territories, Canada

Abstract: Elevated levels of arsenic (As) and antimony (Sb) in water and sediments are legacy residues found downstream from gold-mining activities at the Giant Mine in Yellowknife, Northwest Territories (NWT), Canada. To track the transport and fate of As and Sb, samples of mine-waste from the mill, and surface water, sediment, pore-water, and vegetation downstream of the mine were collected. Mine waste, porewater, and sediment samples were analyzed for bulk chemistry, and aqueous and solid-state speciation. Sediment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(56 citation statements)
references
References 74 publications
5
51
0
Order By: Relevance
“…Fast reductive precipitation of Sb agrees with the absence of aqueous Sb (III) and the co-existence of Sb(V) with As(III) in the experimental solutions of Exp. II and III, as previously demonstrated in other studies (Casiot et al, 2007;Fawcett et al, 2015;Mitsunobu et al, 2006). The model fit to the experimental data requires a two-step process: sorption of Sb(V) followed by its reduction at the mineral surfaces, presumably via a detoxification pathway (Table 2, R 21 ).…”
Section: Fate Of Sb In the Presence Of Microorganismssupporting
confidence: 56%
See 1 more Smart Citation
“…Fast reductive precipitation of Sb agrees with the absence of aqueous Sb (III) and the co-existence of Sb(V) with As(III) in the experimental solutions of Exp. II and III, as previously demonstrated in other studies (Casiot et al, 2007;Fawcett et al, 2015;Mitsunobu et al, 2006). The model fit to the experimental data requires a two-step process: sorption of Sb(V) followed by its reduction at the mineral surfaces, presumably via a detoxification pathway (Table 2, R 21 ).…”
Section: Fate Of Sb In the Presence Of Microorganismssupporting
confidence: 56%
“…3: h). Recent studies have demonstrated that under anoxic conditions, Sb(V) can act as a TEA for microbial respiration (Abin and Hollibaugh, 2014), but also that Sb(V) respiration is inhibited by the presence of aqueous As(V) (Fawcett et al, 2015;Kulp et al, 2014;Mitsunobu et al, 2006). Thus, Sb(V) respiration could explain the increase of ATP observed in Exp.…”
Section: Fate Of Sb In the Presence Of Microorganismsmentioning
confidence: 92%
“…Arsenic is a well-known toxic element; therefore, human exposure to gold mine tailings by inhalation or ingestion is a health hazard that can result in a variety of diseases including various forms of cancer, cardiovascular and peripheral diseases (Hopenhyan-Rich et al 1996;Kaltreider et al 2001;Walker et al 2009). In addition, Gold mine tailings represent a source of potential or observed groundwater and surface water contamination in Canada Fawcett et al 2015) and elsewhere in the world (Rösner and Schalkwyk 2000;Kiventerä et al 2016). …”
Section: Introductionmentioning
confidence: 97%
“…Microorganisms and their metabolic processes are very important parts of biogeochemical cycles of chemical elements. They significantly affect mobility, toxicity, bioavailability a solubility of potentially toxic metals and metalloids in the environment (FAWCETT et al 2015). Balance between mobility and immobilization of chemical elements, including arsenic and antimony, is affected mainly by microorganisms, their surrounding environment and physic-chemical conditions of this environment.…”
Section: Introductionmentioning
confidence: 99%